Danfrie Reconsidered. Philippe Danfrié's (d. 1606) Civilite Types. (17th March 2020) - Vervliet, Hendrik D L
Abstract: Though little known to the general public, to type historians Philippe Danfrie (c. 1532–1606) will be recognized as a competitor to Robert Granjon's claim for being the inventor of the first Civilité type, a mid-sixteenth-century gothic script type that superseded the French bâtarde . The bâtarde was the usual script for vernacular texts north of the Alps (with the exception of German speaking countries): authors such as Caxton or Rabelais were read in this script. In their Civilité Types (Oxford, 1966) Carter & Vervliet described five of Danfrie's founts. This article aims to present an update of their work and to expand it with four more founts. Danfrie's civil career is broadly documented and that may be a help for gaining a closer insight in the characteristics of a late sixteenth-century type production that balanced between an incunabular model of private type ownership and the seventeenth-century norm of sales of cast types through large monopolistic typefoundries.